Performance, endocrine, metabolic, and reproductive responses of Nellore heifers submitted to different supplementation levels pre- and post-weaning - Silva, Aline Gomes da; Paulino, Mário Fonseca; Amorim, Lincoln da Silva; Detmann, Edenio; Moura, Felipe Henrique de; Manso, Marcos Rocha; Paiva, Paulo Henrique Silva e; Ortega, Román Enrique Maza; Melo, Luciano Prímola de; Rennó, Luciana Navajas (Tropical Animal Health and Production, 2017)
The present study was conducted to evaluate the effects of high and low supplementation levels pre- and post-weaning on performance, endocrine, metabolic, and reproductive responses of Nellore heifers. Fifty Nellore heifers with 132 ± 9.9 kg average body weight (BW) and 138 ± 19 days of age were supplemented from 4 to 14 months. The heifers were distributed into five supplementation plans: HH—6 g/kg of BW of supplement pre- and post-weaning, HL—6 g/kg of BW of supplement pre-weaning and 3 g/kg post-weaning, LH—3 g/kg of BW pre-weaning and 6 g/kg of BW post-weaning, LL—3 g/kg of BW pre- and post-weaning, and CC—control, no supplementation. Interactions were not significant (P > 0.10). The level of supplement fed pre-weaning did not affect any of the performance variables evaluated at the end of the experiment (P > 0.10). There was a significant effect of supplementation and level of supplementation fed post-weaning on average daily gain (ADG) and final BW (P < 0.05). Overall ADG was also affected only by supplementation and level of supplement fed post-weaning (P < 0.05) with animals receiving 6 g/kg of BW post-weaning gaining more weight. Follicular diameter was greater in animals that received 6 g/kg of BW post-weaning (P < 0.05). In summary, performance, endocrine, metabolic, and reproductive variables evaluated in the current study were improved by the level of supplement fed post-weaning. Heifers receiving supplementation of 6 g/kg of BW post-weaning had greater responses, independent of the level received during the pre-weaning phase.
Keywords: Biometry; Growth hormone; Insulin; Ruminant metabolism